Fallstudie av 10 skånska gårdar för en lönsam stutproduktion - Bäcklund, Nina (2007)
During the summer of 2005 a number of steer producers in Skåne, Sweden, found that their animals graded less favourable according to the EUROP carcass grading system when slaughtered, than ordinary. The aim with this project was to determine factors that affects the production result in steer production and to find the reason to the lower classification. The project was initiated by Anita Persson, LRF, Skåne and was preformed with supervision from Ingemar Olsson, SLU, and Jens Fjelkner, Skånesemin. Ten producers of dairy steers located in Skåne was chosen for this study. The producers were interviewed to collect information about their steer production with respect to their planning and results.